Is Global Microbial Biodiversity Increasing, Decreasing, or Staying the Same? - Thaler, David S. (Frontiers in Ecology and Evolution, 2021)
Animal and Plant biodiversity is decreasing. In contrast, the global direction and the pace of change in microbial biodiversity, including viral diversity, are complete unknowns. Important niches for microbial diversity occur in highly specific associations with plants and animals, these niches are lost as hosts become extinct. On the other hand, much of the context of microbial life is in the context of other microbes. Darwin's tangled bank for microbes may be composed mostly of other microbes. Survey approaches are too slow for microbes. Single molecule sequencing studies in populations may directly measure the pace of microbial evolution.